Effects Of Time-restricted Eating With Different Eating Duration On Anthropometrics And Cardiometabolic Health: A Systematic Review And Meta-analysis - Mazuin Kamarul Zaman; Nur Islami Mohd Fahmi Teng; Sazzli Shahlan Kasim; Norsham Juliana; Mohammed Abdullah Alshawsh (Baishideng Publishing Group Inc, 2024)
Indexed by WOS/ Scopus